2020
DOI: 10.1016/j.jmmm.2020.166424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in molecular spin clusters and their assemblies: Exact and Monte Carlo studies using exact cluster eigenstates

Abstract: We study the magnetocaloric effect (MCE) in spin clusters of six spins with site spins s = 1, 3/2 and 2 for different exchange anisotropies. We also study MCE in an assembly of spin clusters, on a chain, a 2-D square lattice and a 3-D cubic lattice with spin-dipolar interactions using a Monte Carlo method in spin-1 systems. We compute the magnetic Grüneisen parameter Γ H , and study its dependence on exchange anisotropy and spin-dipolar interaction. With increase of exchange anisotropy the maxima in Γ H , shif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition to classical Ising model-based studies, quantum Heisenberg model has also been investigated by exact methods in the context of zero-dimensional cluster geometry, e.g. cube [45], a cuboctahedron [46], an edge-sharing tetrahedron [47], a hexagon [48], or a finite chain [49] clusters. Exact studies of Heisenberg model for particular molecular systems can also be found in the literature, e.g., a butterfly-shaped structure with higher spin [50] or our previous study concerning a structure with two interacting triangles [51].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to classical Ising model-based studies, quantum Heisenberg model has also been investigated by exact methods in the context of zero-dimensional cluster geometry, e.g. cube [45], a cuboctahedron [46], an edge-sharing tetrahedron [47], a hexagon [48], or a finite chain [49] clusters. Exact studies of Heisenberg model for particular molecular systems can also be found in the literature, e.g., a butterfly-shaped structure with higher spin [50] or our previous study concerning a structure with two interacting triangles [51].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment revealed isentropes with a rich structure, which were very well reproduced theoretically by considering a simple Heisenberg spin Hamiltonian with only exchange [17] or including also intramolecular dipolar interactions [18]. The observed isentropes were concluded to be a direct manifestation of the trigonal antiferromagnetic net structure, which triggered further experimental [19,20] and theoretical [21][22][23][24][25][26][27][28][29][30][31] studies of mainly frustration-enhanced MCE in finite systems of various shapes and topologies. They included geometrically frustrated Ising spin clusters with shapes of regular polyhedra [21,22] or triangular geometry [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 54%
“…The main focus of molecular magnetism has, therefore, been on raising the blocking temperature for magnetization relaxation by increasing the magnetic anisotropy barrier. Several earlier studies focused on analyzing the effect of on-site anisotropy as well as exchange anisotropy on the magnetic anisotropy barrier [8][9][10][11]. Single-chain magnets (SCMs) were subsequently synthesized, with the expectation that they will have a higher blocking temperature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%